Role of wnt/beta-catenin signaling in ovarian tumour growth and angiogenesis. A crosstalk with Notch system - Bocchicchio, Sebastian (2019)
Wnt/β-catenin and Notch are highly conserved pathways that regulate a diversity of cell processes, including proliferation, apoptosis and differentiation. We analyzed the role of both systems in ovarian cancer using specific inhibitors. For this purpose we performed three in vivo experiments. A human ovarian adenocarcinoma cell line (IGROV-1) was subcutaneously injected in 6-8 weeks-old female nude mice. Once the tumours were palpable, we injected the inhibitors: the first and second experiments were carried out using Wnt/β-catenin inhibitors (XAV939: 2.5, 5 mg/kg; ICG-001: 5 and10 mg/kg). The third experiment was a combination of ICG-001 (5mg/kg) and DAPT (5 mg/kg), a Notch inhibitor. Mice were injected every two days three times and they were euthanized 3 days after the last injection. Our results showed a significant decrease in tumour size when mice were treated either with XAV939 or with ICG-001. When compared with tumours from non-treated animals, both experiments showed a significant decrease in cell proliferation (KI67) and a decrease in the endothelial and periendothelial cell area stained with CD31 and α-Smooth-muscle-actin, respectively. When mice were treated with XAV939, a significant decrease in VEGF levels and Angiopoietin 1/2 was observed. Regarding the experiment with the combination of inhibitors, there was a significant decrease in tumour size and a decline in tumour cell proliferation (KI67). Both inhibitors administered simultaneously produced a decrease in cell proliferation at the same extent as individually administrated. In conclusion, we demonstrate a clear involvement of Wnt/β-catenin in ovarian tumour growth and angiognesis. We suggest an interaction of this pathway with Notch system.